Pengaruh Pemberian Kombinasi Pupuk Organik dan Anorganik Terhadap Keragaan Pertumbuhan dan Tanaman Jahe Merah (Zingiber Officinale Rubrum.) di Kecamatan Majalaya Kabupaten Karawang - Wagiono; Dessy Agustina Sari; Sabrina Alfiansyahri Miledhiya; Ismi Ari Fitria; Kristin Valentina Sidabutar; Muhammad Ikhsan Kamil; Al Ghifari Marendra Fadzrin (Faculty of Agriculture University of Singaperbangsa Karawang, 2020)
This research aim is to provide information about impact of combination manure and inorganic fertilizer application to growth and yields performance of red ginger plants cultivated in pandemic Covid-19 period. The research was conducted in Majalaya sub-district of Karawang District, from March to October 2020. The research used experiment method and Randomized Block Design (RDB) as it experimental design which was arranged single factor, that are combination of manure and fertilizer (4 treatment) each repeated 6 times. The best growth in vegetative phase of red ginger crop aged 6 months after planting is P1 (combination of 0,5 kg/polybag treatment of manure, 7,5 g/polybag treatment Urea, 5,0 g/polybag treatment of KCl, and 5,0 g/polybag treatment of SP36) but not significantto P4 treatment (combination of 1,0 kg/polybag treatment of manure, 3,75 g/polybag treatment Urea, 2,5 g/polybag treatment of KCl, and 2,5 g/polybag treatment of SP36) fo reach plant height parameters of 39.2 cm and 37,9 cm, and each stem diameter of 24 mm and 23 mm. Treatment of P1 yielded the highest fresh rhizome weight 450,2 and 439,8 gram/ clump at 8 month after planting. Decreasing of inorganic fertilizer to 50% and increasing of manure t0 100% in Entisol would be growth and yields of red ginger crop are not significant if it compares to standard combination fertilizer and manure application.